Efektivitas Edukasi Posyandu dalam Meningkatkan Kesadaran Imunisasi Wajib pada Ibu Balita: Studi di Wilayah Puskesmas Umbansari - Indah Permata Sari, Septi; Susilawati, Elly; Yanti, Yanti (Poltekes Kemenkes Tanjungpinang, 2025)
Immunization is one of the most effective preventive efforts in reducing morbidity and mortality caused by infectious diseases in children under five years of age. Although the immunization program has long been implemented by the government, a lack of awareness among some mothers regarding the importance of mandatory immunization is still observed. This may be due to limited access to information, misconceptions, or insufficient health education. This community service activity aimed to enhance the understanding of mothers of toddlers about the importance of immunization through an educational approach conducted directly at the Integrated Health Post (Posyandu) within the working area of Umbansari Public Health Center. The activity involved health education sessions, interactive discussions, and the distribution of educational media such as leaflets. The primary target was mothers with children aged 0–5 years. The results showed a significant improvement in knowledge, with the average pre-test score increasing from 60 to 80 in the post-test. These findings indicate the effectiveness of community-based educational approaches in raising mothers' awareness about the importance of mandatory immunization. It is expected that similar activities can be implemented sustainably as part of strategies to improve the coverage of basic immunization programs.